Rhenium and osmium isotope and elemental behaviour accompanying laterite formation in the Deccan region of India - Wimpenny, J; Gannoun, A; Burton, K; Widdowson, M; James, R; Gislason, SR (2007)
This study presents major-, trace-element and Re-Os isotope data for two laterite profiles from the Deccan region in India. The first profile from Bidar developed upon Deccan basalt itself, the second from Goa formed on an Archean greywacke. Both profiles show the typical changes in mineralogy and chemistry accompanying laterite formation; from little altered parent rock at depth, to altered saprolite (depleted in mobile elements), to a highly altered, Si depleted, Fe-rich laterite capped by an iron-rich crust at the surface. Rhenium and Os concentrations show a systematic enrichment with increasing degree of alteration, where the highest concentrations are found in the Fe-rich laterite crust. The level of Os enrichment is greater than that of Re, and as a consequence 187Re/188Os ratios are lower in the laterite than the parent rock. With time this leads to the development of 187Os/188Os ratios that are also less radiogenic than the parent rock, and this relationship holds irrespective of rock type or age or the time of laterite formation. The marked enrichment of both Re and Os, and the patterns of change above and below the paleowatertable, indicates that both elements are highly mobile. High Eh and low pH conditions facilitate Re and Os dissolution, and redistribution occurs via groundwaters, whereas with increasing pH (higher in the profile) both elements are scavenged out of solution and precipitate either as PGE-rich alloys or are strongly partitioned into oxides or oxyhydroxides. Nevertheless, the isotope and elemental data for both profiles suggests that at least some of the Re and Os must be externally derived, either from aeolian deposition or from the lateral movement of solute-laden groundwaters. Given the high levels of Os in laterites, their extensive geographical coverage of the continents, and their active role in the surface water cycle, it seems likely that they will exert a significant influence on the continental flux of Os to the oceans, that will, in turn, be sensitive to tectonic or climatic change. © 2007 Elsevier B.V. All rights reserved.